Soft Computing: Theories and Applications Proceedings of SoCTA 2017 - Ray, Kanad; Sharma, Tarun K.; Rawat, Sanyog; Saini, R. K.; Bandyopadhyay, Anirban (Advances in Intelligent Systems and Computing,, 2019)
The book focuses on soft computing and its applications to solve real-world problems occurring in different domains ranging from medicine and healthcare, and supply chain management to image processing and cryptanalysis. It includes high-quality papers presented in the International Conference on Soft Computing: Theories and Applications (SoCTA 2017), organized by Bundelkhand University, Jhansi, India. Offering significant insights into soft computing for teachers and researchers alike, the book inspires more researchers to work in the field of soft computing.